A high-toughness antistatic TPEE comb and preparation method thereof
By combining antistatic agents with TPEE materials and preparing a highly tough antistatic TPEE comb under the action of antioxidants and lubricants, the problem of static electricity and scratches in existing plastic combs when combing their hair is solved. Achieve better flexibility and anti-static effects.
Patent Information
- Application Number
- CN202410094191.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-01-23
AI Technical Summary
Existing plastic combs are prone to static electricity when combing their hair, causing hair to fly, dry, knotted and easily broken, and may scratch the scalp or hair.
A comb made of TPEE material is prepared by combining with antistatic agents, antioxidants and lubricants to prepare a TPEE comb with antistatic, anti-bending fatigue, low temperature compliance and flexibility.
Reduces the possibility of static electricity generated by the comb when used, avoids scratching the scalp or hair, and improves the toughness and practicality of the comb.
Smart Images

Figure BDA0004677980890000091 
Figure BDA0004677980890000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and more specifically, to a high-toughness antistatic TPEE comb and a preparation method thereof. Background Art
[0002] A comb is a tool for combing hair. There are many types of combs, mainly divided into wooden combs, metal combs and plastic combs. Among them, common wooden combs such as sandalwood combs, jujube wood combs, peach wood combs, horn combs, etc. are relatively expensive and require special maintenance. They cannot be soaked in water for a long time, exposed to the sun or placed in high temperatures. Metal combs such as stainless steel combs, aluminum alloy combs, copper combs, silver combs, etc. are harder in texture and are prone to making noise when combing hair. They are not suitable for combing hair for a long time, and are prone to scratching the scalp or causing hair to break easily when used.
[0003] Plastic combs are the most common type of combs. They are cheap, light and easy to clean. They are usually not easily damaged and do not require special maintenance. However, most plastics are insulated. Therefore, in autumn and winter, when people wear more clothes, hair is prone to static electricity when it comes into contact with sweaters, down, etc. When combing hair, static electricity is also easily generated, causing hair to fly, which may make hair drier, tangled and easy to break. At present, most plastic combs are made of PE, PP, PC, ABS and other materials. The materials are hard and may irritate the scalp and cause discomfort when used. At the same time, the teeth of plastic combs may scratch the hair and cause hair damage. Summary of the invention
[0004] In order to reduce static electricity generated by a comb when combing hair, and at the same time obtain better flexibility and avoid the comb scratching the scalp or hair, the present application provides a high-toughness antistatic TPEE comb and a preparation method thereof.
[0005] In the first aspect, a high-toughness antistatic TPEE comb comprises the following raw materials in parts by weight: 80-100 parts of TPEE
[0006] Antistatic agent 10-30 parts
[0007] Antioxidant 0.1-0.5 parts
[0008] 1-3 parts of lubricant.
[0009] TPEE is a block copolymer containing polyester hard segment and polyether soft satin. It has the characteristics of rubber and thermoplastics. Its hardness and flexibility are adjustable, so it has better toughness, elasticity, softer texture, and good compliance at low temperature. The antistatic agent has an antistatic effect, the antioxidant improves the anti-aging effect of the material, and the lubricant has a lubricating effect, which improves the convenience of processing and makes the TPEE comb easy to demold.
[0010] Therefore, by compounding the antistatic agent with TPEE, and under the action of antioxidants and lubricants, the TPEE comb has better antistatic effect, anti-bending fatigue, good low-temperature compliance and good flexibility. Therefore, when combing hair in autumn and winter, it is not easy to generate static electricity, and it is not easy to scratch the scalp or hair. It also has a certain strength and is easy to manage hair, which improves the practicality of TPEE.
[0011] The TPEE comb of the present application is moderately soft and hard, easy to comb hair and will not cause damage to hair or scalp. Compared with wooden combs, the TPEE comb is easy to maintain and has better toughness, is not easy to be damaged, and is not easy to damage scalp or hair; compared with metal combs, it is moderately soft and hard, and is not easy to damage scalp or hair; compared with current plastic combs, it has better anti-static effect, is flexible, and is not easy to damage scalp or hair.
[0012] Preferably, the antistatic agent is composed of the following raw materials in parts by weight:
[0013] Expanded graphite powder 5-10 parts
[0014] Organic polyborosilazane 0.3-0.5 parts
[0015] Silane coupling agent 0.1-0.5 parts
[0016] 2-5 parts of polycaprolactone derivatives.
[0017] Expanded graphite powder is obtained by expanding graphite. Its appearance is worm-like, loose, porous and curved. The worm-like graphite can be embedded in each other, which improves its softness, resilience and plasticity. It also has the function of reinforcement and conductivity. Organic polyborosilazane has good adhesion and film hardness, so it can play a role in toughening and reinforcement.
[0018] Silane coupling agent has a coupling effect, which improves the compatibility of expanded graphite in the principle system, and polycaprolactone derivatives are derivatives obtained by grafting and modification of polycaprolactone. Polycaprolactone has better softness, and the polycaprolactone derivatives obtained after grafting have better softness and film-forming properties. Therefore, it is easy to form a film, and combined with expanded graphite powder, organic polyborosilazane, and silane coupling agent, the antistatic agent obtained has better toughness and antistatic properties. Therefore, after compounding with TPEE, the TPEE comb obtained has good flexibility, high toughness, good low-temperature compliance, good antistatic properties, and good resistance to bending fatigue, etc., which reduces the possibility of static electricity generated by the TPEE comb during use. At the same time, it is moderately soft and hard, which reduces the damage to the scalp or hair when combing the hair, and also reduces the possibility of TPEE breaking, improving the practicality of the TPEE comb.
[0019] Preferably, the expanded graphite powder consists of the following particle size ranges:
[0020] 150-200 mesh expanded graphite powder 1-5 parts
[0021] 2-5 parts of 220-250 mesh expanded graphite powder
[0022] 2-8 parts of 300-500 mesh expanded graphite powder.
[0023] The expanded graphite powder in the above mesh range is mixed to obtain expanded graphite powder, which is easy to mix evenly with the raw material system of the antistatic agent and can give better conductivity. Compared with the expanded graphite of a single particle size, it has better softness, resilience and plasticity. Therefore, after compounding with organic polyborosilazane silicon, alkane coupling agent, and polycaprolactone derivative, the raw material system of the antistatic agent for TPEE comb is obtained, which can further improve its toughness, antistatic property, resistance to bending fatigue and flexibility. When using the TPEE comb, it is not easy to generate static electricity, and it is not easy to damage the scalp or hair. At the same time, it is not easy to break, etc., which improves the practicality of the comb.
[0024] Preferably, the polycaprolactone derivative is a hydroxypropyl cellulose grafted polycaprolactone copolymer and / or a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer.
[0025] Hydroxypropyl cellulose grafted polycaprolactone copolymer and polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer both have good film-forming properties and flexibility. They are easily soluble in water. After being compounded with a silane coupling agent, they can coat expanded graphite and combine with organic polyborosilazane to make the antistatic agent have better toughness, antistatic properties and softness, thereby further improving the toughness and antistatic effect of TPEE combs.
[0026] Preferably, the hydroxypropyl cellulose grafted polycaprolactone copolymer and the polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer are used in a ratio of (2-3):1.
[0027] When the present application uses hydroxypropyl cellulose grafted polycaprolactone copolymer and polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer for compounding, a synergistic effect is achieved, thereby further improving the flexibility and antistatic effects of the TPEE comb.
[0028] Preferably, the silane coupling agent is one or more of 3-isocyanate propyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and N-β-(aminoethyl)-γaminopropyl trimethoxy silane.
[0029] The above 3-isocyanate propyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and N-β-(aminoethyl)-γaminopropyl trimethoxysilane all have a coupling effect, and are combined with polycaprolactone derivatives to easily form a soft coating film on the surface of expanded graphite. When combined with organic polyborosilazane, the obtained antistatic agent can be used in the raw material system of TPEE, so that the prepared TPEE comb has better flexibility, antistatic effect and anti-bending fatigue, etc., thereby reducing the generation of static electricity, damage to the scalp or hair, or breakage and damage during the use of the TPEE comb, thereby improving the practicality of the TPEE comb.
[0030] Preferably, the silane coupling agent is composed of 3-isocyanate propyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and N-β-(aminoethyl)-γaminopropyl trimethoxy silane in a dosage ratio of 1: (0.5-1.2): (0.8-1.8).
[0031] When 3-isocyanate propyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane are compounded, a synergistic effect is achieved, and under the action of polycaprolactone derivatives and organic polyborosilazane, the TPEE comb obtains better flexibility and antistatic effects. Therefore, the static electricity generated by the TPEE comb during use can be further reduced, reducing scratches on the scalp or hair.
[0032] Preferably, the antistatic agent is prepared by the following method:
[0033] According to weight, a polycaprolactone derivative is weighed and dissolved in a solvent, and then a silane coupling agent is added and stirred for 30-50 minutes. Then, expanded graphite powder is added and vibrated for 1-3 hours. The solvent is removed to obtain a mixture, and then organic polyborosilazane is added and mixed with the mixture, and stirred for 20-30 minutes to obtain an antistatic agent.
[0034] The preparation method is simple to operate. The polycaprolactone derivative is dissolved and then combined with a silane coupling agent to form a coating film on the expanded graphite powder. After vibrating for 1-3 hours, part of the polycaprolactone derivative and the silane coupling agent enter the expanded graphite powder. After removing the solvent, the expanded graphite powder has a flexible coating film inside and outside. The polyborosilazane is compounded to obtain an antistatic agent, which is used in the raw material system of the TPEE comb, so that the TPEE comb has better flexibility and antistatic effects. Therefore, the static electricity generated by the TPEE comb during use can be further reduced, the scratching of the scalp or hair can be reduced, and the practicality of the comb can be improved.
[0035] Preferably, the antioxidant is one or more of antioxidant 702, antioxidant 703, and antioxidant 1010; and the lubricant is one of polyethylene wax and paraffin wax.
[0036] In the second aspect, the present application provides a method for preparing a high-toughness antistatic TPEE comb, using the following technical solution:
[0037] According to parts by weight, TPEE is dehydrated at a temperature of 90-98° C. for 2-3 hours to obtain dehydrated TPEE; then the dehydrated TPEE, antistatic agent, antioxidant and lubricant are weighed and mixed evenly, heated to melt, stirred for 20-30 minutes, extruded, granulated and injection molded to obtain a TPEE comb.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. By using TPEE material as the main base material, it has the characteristics of rubber and thermoplastics, so it has better toughness, elasticity, good low-temperature compliance and resistance to bending fatigue, and the antistatic agent has better antistatic effect. Therefore, the antistatic agent is compounded with TPEE, and under the action of antioxidants and lubricants, the prepared TPEE comb has better antistatic effect, resistance to bending fatigue, good low-temperature compliance and good flexibility. Therefore, when combing your hair in autumn and winter, it is not easy to generate static electricity, and it is not easy to scratch the scalp or hair.
[0040] 2. The antistatic agent prepared by the present application through polycaprolactone derivatives, expanded graphite powder, organic polyborosilazane, and silane coupling agent has better toughness and antistatic properties. Therefore, after compounding with TPEE, the prepared TPEE comb has good flexibility, high toughness, good low-temperature compliance, good antistatic properties, and good resistance to bending fatigue, etc., which reduces the possibility of static electricity generated by the TPEE comb during use. At the same time, it is moderately soft and hard to reduce damage to the scalp or hair when combing the hair, and also reduces the possibility of TPEE breakage, thereby improving the practicality of the TPEE comb. DETAILED DESCRIPTION
[0041] The present application is further described in detail below with reference to the embodiments.
[0042] The preferred commercial antistatic agent manufacturer is Qingdao Enze Chemical Co., Ltd., model number is Z101;
[0043] The average molecular weight of TPEE is 1500-2000;
[0044] The expansion multiple of expanded graphite powder is 200-250;
[0045] The preferred manufacturer of organic polyborosilazane is Anhui IOTA Silicone Oil Co., Ltd., model number is IOTA;
[0046] The preferred manufacturer of hydroxypropyl cellulose grafted polycaprolactone copolymer is Xi'an Ruixi Biotechnology Co., Ltd. The average molecular weight is 2000-5000;
[0047] The invention relates to a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the average molecular weight of the polyethylene glycol is 200-400; and the average molecular weight of the polycaprolactone is 1000-2000.
[0048] Preparation example of antistatic agent
[0049] Preparation Example 1
[0050] An antistatic agent is prepared by the following method:
[0051] 2 kg of polycaprolactone derivative was weighed and dissolved in anhydrous ethanol, and then 0.1 kg of silane coupling agent was added, and the mixture was stirred at a speed of 50 r / min for 30 min, and then 5 kg of expanded graphite powder was added, and the mixture was vibrated in 40 Hz ultrasound for 1 h, and the anhydrous ethanol was removed by reduced pressure distillation to obtain a mixture, and then 0.3 kg of organic polyborosilazane was added to the mixture and mixed, and the mixture was stirred at a speed of 50 r / min for 20 min to obtain an antistatic agent.
[0052] The polycaprolactone derivative is a hydroxypropyl cellulose grafted polycaprolactone copolymer.
[0053] The silane coupling agent is 3-isocyanatepropyltrimethoxysilane.
[0054] The expanded graphite powder is obtained by mixing 150-mesh expanded graphite powder, 220-mesh expanded graphite powder and 300-mesh expanded graphite powder in a dosage ratio of 1:2:2.
[0055] Preparation Example 2
[0056] The difference between Preparation Example 2 and Preparation Example 1 is that the antistatic agent is prepared by the following method:
[0057] 4 kg of polycaprolactone derivative was weighed and dissolved in anhydrous ethanol, and then 0.3 kg of silane coupling agent was added, and the mixture was stirred at a speed of 50 r / min for 30 min, and then 8 kg of expanded graphite powder was added, and the mixture was vibrated in 40 Hz ultrasound for 2 h, and the anhydrous ethanol was removed by vacuum distillation to obtain a mixture, and then 0.4 kg of organic polyborosilazane was added to the mixture and mixed, and the mixture was stirred at a speed of 50 r / min for 25 min to obtain an antistatic agent.
[0058] Preparation Example 3
[0059] The difference between Preparation Example 3 and Preparation Example 1 is that the antistatic agent is prepared by the following method:
[0060] 5 kg of polycaprolactone derivative was weighed and dissolved in anhydrous ethanol, and then 0.5 kg of silane coupling agent was added, and the mixture was stirred at a speed of 50 r / min for 40 min, and then 10 kg of expanded graphite powder was added, and the mixture was vibrated in 40 Hz ultrasound for 3 h, and the anhydrous ethanol was removed by vacuum distillation to obtain a mixture, and then 0.5 kg of organic polyborosilazane was added to the mixture and mixed, and the mixture was stirred at a speed of 50 r / min for 30 min to obtain an antistatic agent.
[0061] Preparation Example 4
[0062] The difference between Preparation Example 4 and Preparation Example 2 is that the polycaprolactone derivative is a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer.
[0063] Preparation Example 5
[0064] The difference between Preparation Example 5 and Preparation Example 2 is that the expanded graphite powder is obtained by mixing 200-mesh expanded graphite powder, 250-mesh expanded graphite powder, and 300-mesh expanded graphite powder in a dosage ratio of 2:3:5.
[0065] Preparation Example 6
[0066] The difference between Preparation Example 6 and Preparation Example 2 is that the expanded graphite powder is obtained by mixing 200-mesh expanded graphite powder, 250-mesh expanded graphite powder, and 300-mesh expanded graphite powder in a dosage ratio of 5:5:8.
[0067] Preparation Example 7
[0068] The difference between Preparation Example 7 and Preparation Example 5 is that the polycaprolactone derivative is obtained by mixing a hydroxypropyl cellulose grafted polycaprolactone copolymer and a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer in a dosage ratio of 2:1.
[0069] Preparation Example 8
[0070] The difference between Preparation Example 8 and Preparation Example 5 is that the polycaprolactone derivative is obtained by mixing a hydroxypropyl cellulose grafted polycaprolactone copolymer and a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer in a dosage ratio of 3:1.
[0071] Preparation Example 9
[0072] The difference between Preparation Example 9 and Preparation Example 7 is that the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0073] Preparation Example 10
[0074] The difference between Preparation Example 10 and Preparation Example 7 is that the silane coupling agent is N-β-(aminoethyl)-γaminopropyltrimethoxysilane.
[0075] Preparation Example 11
[0076] The difference between Preparation Example 11 and Preparation Example 7 is that the silane coupling agent is a mixture of 3-isocyanatepropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-β-(aminoethyl)-γaminopropyltrimethoxysilane in a dosage ratio of 1:0.5:0.8.
[0077] Preparation Example 12
[0078] The difference between Preparation Example 12 and Preparation Example 7 is that the silane coupling agent is 3-isocyanatepropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-β-(aminoethyl)-γaminopropyltrimethoxysilane mixed in a dosage ratio of 1:1.2:1.8.
[0079] Preparation Comparative Example
[0080] Preparation Comparative Example 1
[0081] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the polycaprolactone derivative is replaced by an equal amount of a silane coupling agent.
[0082] Preparation Comparative Example 2
[0083] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that the silane coupling agent is replaced by an equal amount of a polycaprolactone derivative.
[0084] Preparation Comparative Example 3
[0085] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that the organic polyborosilazane is replaced by an equal amount of a silane coupling agent.
[0086] Preparation Comparative Example 4
[0087] The difference between Preparation Comparative Example 4 and Preparation Example 1 is that the antistatic agent is 150 mesh expanded graphite powder.
[0088] Preparation Comparative Example 5
[0089] The difference between the comparative example 5 and the preparation example 1 is that the expanded graphite powder is 20 kg
[0090] Example
[0091] Example 1
[0092] A high-toughness antistatic TPEE comb is prepared by the following method:
[0093] The TPEE was dehydrated at a temperature of 98°C for 2 hours to obtain dehydrated TPEE; 8 kg of dehydrated TPEE, 1 kg of a commercially available antistatic agent, 0.01 kg of an antioxidant 1010 and 0.1 kg of polyethylene wax were weighed and put into a high-speed mixer, and stirred at a speed of 200 r / min for 10 minutes to mix the materials evenly, and then transferred to a kneader and heated to 150°C to melt the materials, and stirred at a speed of 80 r / min for 30 minutes to obtain a molten material, which was then transferred to an extruder for extrusion, granulated by a granulator, and the obtained pellets were put into an injection molding machine for injection molding to obtain a TPEE comb.
[0094] Example 2
[0095] The difference between Example 2 and Example 1 is that the TPEE comb is made by the following method:
[0096] The TPEE was dehydrated at a temperature of 95°C for 2.5 hours to obtain dehydrated TPEE; 9 kg of dehydrated TPEE, 2 kg of a commercially available antistatic agent, 0.03 kg of antioxidant 1010 and 0.2 kg of polyethylene wax were weighed and put into a high-speed mixer, stirred at a speed of 200 r / min for 10 minutes to mix the materials evenly, then transferred to a kneader and heated to 150°C to melt the materials, stirred at a speed of 80 r / min for 30 minutes to obtain a molten material, then transferred to an extruder for extrusion, granulated by a granulator, and the obtained pellets were put into an injection molding machine for injection molding to obtain a TPEE comb.
[0097] Example 3
[0098] The difference between Example 3 and Example 1 is that the TPEE comb is made by the following method:
[0099] TPEE was dehydrated at a temperature of 90°C for 2 hours to obtain dehydrated TPEE; 10 kg of dehydrated TPEE, 3 kg of a commercially available antistatic agent, 0.05 kg of an antioxidant 1010 and 0.3 kg of paraffin were weighed and put into a high-speed mixer, stirred at a speed of 200 r / min for 10 minutes to mix the materials evenly, then transferred to a kneader and heated to 150°C to melt the materials, stirred at a speed of 80 r / min for 30 minutes to obtain a molten material, then transferred to an extruder for extrusion, granulated by a granulator, and the obtained pellets were put into an injection molding machine for injection molding to obtain a TPEE comb.
[0100] Example 4-20
[0101] The difference between Example 4-20 and Example 1 is that the source of the antistatic agent is different, as shown in Table 1 below;
[0102] Table 1 Sources of antistatic agents for Examples 4-20
[0103] Example Sources of antistatic agents Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Example 4 Example 8 Preparation Example 5 Example 9 Preparation Example 6 Example 10 Preparation Example 7 Embodiment 11 Preparation Example 8 Example 12 Preparation Example 9 Embodiment 13 Preparation Example 10 Embodiment 14 Preparation Example 11 Embodiment 15 Preparation Example 12 Example 16 Preparation Comparative Example 1 Embodiment 17 Preparation Comparative Example 2 Embodiment 18 Preparation Comparative Example 3 Embodiment 19 Preparation Comparative Example 4 Embodiment 20 Preparation Comparative Example 5
[0104] Comparative Example
[0105] Comparative Example 1
[0106] The difference between Comparative Example 1 and Example 1 is that the amount of the antistatic agent used is 5 kg.
[0107] Comparative Example 2
[0108] The difference between Comparative Example 2 and Example 1 is that the amount of antistatic agent used is 35 kg
[0109] Comparative Example 3
[0110] The difference between Comparative Example 3 and Example 1 is that TPEE is replaced by PE in equal amounts.
[0111] Performance testing
[0112] The pellets obtained in Examples 1-20 and Comparative Examples 1-3 were injection molded to obtain corresponding test specimens, and the following performance tests were performed.
[0113] Detection method / test method
[0114] 1. Tensile strength and elongation at break
[0115] Refer to GB / T 1040.1-2018 to test tensile properties and elongation at break.
[0116] 2. Shore hardness
[0117] Refer to GB / T 2411-2008 for Shore hardness testing.
[0118] 3. Flexural modulus
[0119] Refer to GB / T 9341.2008 for testing the flexural modulus.
[0120] 4. Surface resistivity and volume resistivity
[0121] Refer to ASTMD257-2007 standard to test surface resistivity, the test voltage is 500V, and the test time is 1min; refer to GB / T 3048.3-2007 to detect volume resistivity.
[0122] The above tests were all conducted 3 times and the average values were taken. The specific data are shown in Table 2.
[0123] Table 2 Experimental data of Examples 1-20 and Comparative Examples 1-3
[0124]
[0125]
[0126] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that the volume resistivity, elongation at break, and surface resistivity of Example 1 are all higher than those of Comparative Example 1, and the tensile strength, hardness, and flexural modulus are all lower than those of Comparative Example 1, while the volume resistivity, elongation at break, and surface resistivity of Example 1 are all lower than those of Comparative Example 2, and the tensile strength, hardness, and flexural modulus are all higher than those of Comparative Example 1. This indicates that the raw materials and usage ratios of the present application are the preferred choice for the present application.
[0127] By comparing Example 1 and Comparative Example 3 and combining with Table 2, it can be seen that the elongation at break of Example 1 is higher than that of Comparative Example 1, and the tensile strength, hardness and bending modulus are lower than those of Comparative Example 3, indicating that the TPEE comb obtained by the present application has better flexibility and is not easy to damage the scalp.
[0128] By comparing Example 2 with Examples 4-6, it can be seen that the tensile strength, hardness, and bending modulus of Examples 4-6 are improved, while the surface resistivity and volume resistivity are reduced, indicating that the antistatic effect of the antistatic agent prepared by the present application is better.
[0129] By comparing Example 8 with Examples 10-11, it can be seen that the elongation at break of Examples 10-11 is improved, while the tensile strength, flexural modulus, hardness, etc. have no obvious changes, and the surface resistivity and volume resistivity are reduced, indicating that the present application is compounded by hydroxypropyl cellulose grafted polycaprolactone copolymer and polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, and applied in the raw material system of the antistatic agent, which plays a synergistic role, thereby obtaining better flexibility and antistatic properties.
[0130] By comparing Example 10 with Examples 14-15, it can be seen that the elongation at break of Examples 14-15 increases, the hardness and bending modulus decrease, and the tensile strength does not change much, indicating that they have better flexibility, and both the surface resistivity and the volume resistivity are reduced. This indicates that the compounding of 3-isocyanatepropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-β-(aminoethyl)-γaminopropyltrimethoxysilane has a synergistic effect, so that the obtained comb has better toughness and better antistatic effect.
[0131] By comparing Example 4 and Examples 16-18, it can be seen that the surface resistivity and volume resistivity of Examples 16-18 are lower than those of Example 4, and the elongation at break, tensile strength, bending modulus and hardness of Examples 16-18 are significantly changed, indicating that the antistatic agent of the present application is used in the raw material system of the present application, and the obtained TPEE comb has better flexibility and antistatic effect.
[0132] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-toughness antistatic TPEE comb, characterized in that: The invention comprises the following raw materials in parts by weight: TPEE80-100 copies Antistatic agent 10-30 parts Antioxidant 0.1-0.5 parts 1-3 parts of lubricant; The antistatic agent is composed of the following raw materials in parts by weight: Expanded graphite powder 5-10 parts Organic polyborosilazane 0.3-0.5 parts Silane coupling agent 0.1-0.5 parts 2-5 parts of polycaprolactone derivative; The polycaprolactone derivative is a hydroxypropyl cellulose grafted polycaprolactone copolymer and / or a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer; The silane coupling agent is one or more of 3-isocyanate propyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane; The expanded graphite powder consists of the following particle size ranges: 150-200 mesh expanded graphite powder 1-5 parts 2-5 parts of 220-250 mesh expanded graphite powder 2-8 parts of 300-500 mesh expanded graphite powder.
2. A high-toughness antistatic TPEE comb according to claim 1, characterized in that: The polycaprolactone derivative is composed of hydroxypropyl cellulose grafted polycaprolactone copolymer and polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer in a dosage ratio of (2-3):
1.
3. A high-toughness antistatic TPEE comb according to claim 1, characterized in that: The silane coupling agent is composed of 3-isocyanate propyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane and N-β-(aminoethyl)-γaminopropyl trimethoxy silane in a dosage ratio of 1: (0.5-1.2): (0.8-1.8).
4. A high-toughness antistatic TPEE comb according to any one of claims 1 to 3, characterized in that: The antistatic agent is prepared by the following method: According to weight, a polycaprolactone derivative is weighed and dissolved in a solvent, and then a silane coupling agent is added and stirred for 30-50 minutes. Then, expanded graphite powder is added and vibrated for 1-3 hours. The solvent is removed to obtain a mixture, and then organic polyborosilazane is added and mixed with the mixture, and stirred for 20-30 minutes to obtain an antistatic agent.
5. A high-toughness antistatic TPEE comb according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 702, antioxidant 703, and antioxidant 1010; the lubricant is one of polyethylene wax and paraffin wax.
6. A method for preparing a high-toughness antistatic TPEE comb as described in any one of claims 1 to 5, characterized in that: The following steps are involved: According to parts by weight, TPEE is dehydrated at a temperature of 90-98° C. for 2-3 hours to obtain dehydrated TPEE; then the dehydrated TPEE, antistatic agent, antioxidant and lubricant are weighed and mixed evenly, heated to melt, stirred for 20-30 minutes, extruded, granulated and injection molded to obtain a TPEE comb.
Citation Information
Patent Citations
Low-temperature-resistant antistatic thermoplastic elastomer material and preparation method thereof
CN116554629A
Novel comb
CN212729103U